2000
DOI: 10.1210/endo.141.1.7263
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Inhibits Insulin and Glucagon Secretion via Two Receptor Subtypes: An in Vitro Study of Pancreatic Islets from Somatostatin Receptor 2 Knockout Mice*

Abstract: Somatostatin (SST) potently inhibits insulin and glucagon release from pancreatic islets. Five distinct membrane receptors (SSTR1-5) for SST are known, and at least two (SSTR2 and SSTR5) have been proposed to regulate pancreatic endocrine function. Our current understanding of SST physiology is limited by the receptor subtype selectivity of peptidyl SST analogs, making it difficult to assign a physiological function to an identified SST receptor subtype. To better understand the physiology of SSTRs we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
92
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(96 citation statements)
references
References 42 publications
4
92
0
Order By: Relevance
“…Recently, potent, subtype-selective, nonpeptidyl SRIH agonists have been developed and these ligands now provide a means to associate an individual receptor subtype with a biological response [17, 18]. Defining the receptor subtypes involved in ACTH secretion is of particular interest, since SRIH’s effects on growth hormone and insulin release are well documented [19, 20, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, potent, subtype-selective, nonpeptidyl SRIH agonists have been developed and these ligands now provide a means to associate an individual receptor subtype with a biological response [17, 18]. Defining the receptor subtypes involved in ACTH secretion is of particular interest, since SRIH’s effects on growth hormone and insulin release are well documented [19, 20, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, SSTR1 was detected on the axon terminals of hypothalamic neurons extending to the median eminence (13), SSTR4 was found on dendrites in hippocampal neurons (14), and SSTR3 is localized to neuronal cilia in the rodent brain (15). The SSTR5 is of particular pharmacological relevance as this receptor subtype regulates growth hormone secretion from the pituitary as well as insulin secretion from pancreatic ␤-cells (16,17). In the AtT20 cell line, a widely used model for the regulation of hormone release by somatostatin, SSTR2 is present at the cell surface whereas SSTR5 is largely confined to the trans-Golgi-network (TGN, Ref.…”
mentioning
confidence: 99%
“…The effect of SST is mediated through binding to SST receptors of which five different isoforms have been identified (reviewed by Moller et al (2003)). In pancreatic islets, receptors have been identified on both a-and b-cells (Strowski et al 2000, Cejvan et al 2003 and exogenously administered SST inhibits both insulin and glucagon secretion (Schuit et al 1989, Strowski et al 2000, Cejvan et al 2003, findings consistent with a negative regulatory role for SST in islet secretory function. In rodents, this effect is primarily mediated via receptors 5 and 2, respectively, although all five receptors are expressed in the islets (Ludvigsen et al 2004).…”
Section: Introductionmentioning
confidence: 58%
“…In rodents, this effect is primarily mediated via receptors 5 and 2, respectively, although all five receptors are expressed in the islets (Ludvigsen et al 2004). Results from studies using SSTR-deficient mice (SSTR1, SSTR2 or SSTR5) revealed changes in both basal and stimulated insulin secretion (Strowski et al 2000, Wang et al 2005, which is consistent with a role for SST in regulating hormone release. We have recently used islets from SST-deficient mice to demonstrate that SST released from the d-cell exerts a tonic inhibitory input on hormone secretion from both a-and b-cells (Hauge-Evans et al 2009) and it has further been shown that the release of islet SST, like insulin, is stimulated by glucose (Vieira et al 2007, Hauge-Evans et al 2012.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation